Analisis Prinsip Kehati-hatian dalam Proses Pembiayaan pada Perusahaan Pinjaman Online Syariah yang Terdaftar pada Otoritas Jasa Keuangan - Ul-Ashwat, Natasya; Harmoyo, Dwi (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2023)
For this reason, this study discusses about 5C in the financing process for Islamic online loans. The method used is descriptive analysis with a qualitative approach. Data collection techniques using interviews, documentation, online observation. The results of this study explain that: (1) The financing process in Islamic online loans is in accordance with existing theory and has the same flow from starting to register by filling out forms and collecting the files needed, file selection, re-examination, bidding. product, financing approval, realization, then return. (2) Every company has implemented the 5C principle, but on the principle of character and capacity, some companies only analyze online without meeting the prospective borrower directly, while the collateral does not fully guarantee that the prospective borrower is able to complete the financing. (3) Constraints that often occur are data fraud, completeness of data on prospective borrowers and difficulties for the team to decide on appropriate financing.